Evaluasi Performa Website Rumah Sakit CSH Mempergunakan User Acceptance Test - Fauzi, Muhammad Andre; Setyadi, Resad (Politeknik Harapan Bersama, 2025)
User Acceptance Testing (UAT) is a crucial step to ensure that the solutions implemented in a system align with user needs. Unlike system testing, UAT focuses on the functionality of the solution for end users. In this context, testing user acceptance becomes an essential element to assess the performance and user satisfaction of a website. The CSH Hospital website faces the challenge of lacking a scientific analysis to evaluate its performance and usability. Therefore, the UAT method is applied using the ISO 9126 dimensions and the Likert scale. The information system employed facilitates routine transactions, data processing, operational support, and provides relevant information to users. The evaluation results show that the CSH Hospital website achieved a score of 87%, reflecting a high level of user acceptance and comfort in using the website. However, identifying areas for improvement, such as simplifying and accelerating the online registration process, can enhance user experience and streamline services in the future.This aligns with the Sustainable Development Goal (SDG) 3,